Ethyl 4-(2-bromo-5-fluorophenyl)-6-methyl-1-phenyl-2-thioxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title molecule, C(20)H(18)BrFN(2)O(2)S, the pyrimidine ring adopts a flattened envelope conformation. The halogenated benzene ring is orthogonal to the planar part of the pyrimidine ring [dihedral angle = 89.05 (4)°], while the other phenyl ring is oriented at an angle of 85.14 (5)°. The ethoxy group is disordered over two orientations with site occpancies of ca 0.869 (4) and 0.131 (4). Intramolecular C—H⋯Br and C—H⋯O hydrogen bonds generate S(5) and S(6) ring motifs. The crystal structure is stabilized by intermolecular N—H⋯S, C—H⋯F, C—H⋯O and C—H⋯Br hydrogen bonds.